PROPERTIES OF COMPOSITE RESIN ALKASIT AND ZIRCONIA-REINFORCED GLASS-IONOMER CEMENT IN DIFFERENT STORAGE - Vinindya, Clarinda; Pratiwi, Cynthia; Eriwati, Yosi Kusuma; Triaminingsih, Siti; Indrani, Decky J (Odonto : Dental Journal, 2020)
Background: The temperature and salivary pH in a person's mouth are highly dynamic (e.g., before, during, and after eating) and so restorations in a cavity must be resilient to these variable conditions. Temperature and immersion conditions affect the mechanical properties of a restoration. This study aimed to determine the effect of environmental conditions on diametral tensile strength (DTS) and surface microhardness of a resin composite with alkaline fillers or zirconia–reinforced glass ionomer cement (Zr-reinforced GIC). Method: Thirty specimens of a resin composite with alkaline fillers (Cention-N, Ivoclar-Vivadent, Lichtenstein) and 30 specimens with zirconia-reinforced GIC (Zirconomer, Shofu, Japan) were stored at different conditions (23°C and 37°C; with and without immersion in water) for 24 hours. DTS was tested with a Universal Testing Machine (AGS-X series, Shimadzu, Japan) and surface microhardness was tested with a Vickers Microhardness tester (HMV-G Series Micro Vickers Microhardness Tester, Shimadzu, Japan). Data were analyzed statistically using a one-way ANOVA test (and Shapiro-Wilk test. Result: The values of microhardness and DTS increased significantly both for the composite resin alkasite and zirconia-reinforced GIC with increasing temperature in the groups without immersion. However, there was a significant decrease in microhardness and DTS after immersion in distilled water at 37°C for both the composite resin alkasite and zirconia-reinforced GIC. Conclusion: It can be concluded that storage conditions affect the microhardness and DTS of resin composite Alkasite and Zirconia-reinforced GIC